2008
DOI: 10.1002/prep.200800204
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Materials: Crystallization, Characterization and Insensitive Plastic Bonded Explosives

Abstract: The product quality of energetic materials is predominantly determined by the crystallization process applied to produce these materials. It has been demonstrated in the past that the higher the product quality of the solid energetic ingredients, the less sensitive a plastic bonded explosive containing these energetic materials becomes. The application of submicron or nanometric energetic materials is generally considered to further decrease the sensitiveness of explosives. In order to assess the product quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…All samples contain large and distinguishable voids, although their number density may differ. Especially K6 and to a lesser extent K1 contain ‘greyish’ areas, which might be related to the presence of many small inclusions localized in a small volume in the crystal (Watt et al ., ; Van der Heijden et al ., ). The source of the RDX crystals, shock initiation pressure, crystal density and impurity content are reproduced in Table (Watt et al ., ; Doherty & Watt, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples contain large and distinguishable voids, although their number density may differ. Especially K6 and to a lesser extent K1 contain ‘greyish’ areas, which might be related to the presence of many small inclusions localized in a small volume in the crystal (Watt et al ., ; Van der Heijden et al ., ). The source of the RDX crystals, shock initiation pressure, crystal density and impurity content are reproduced in Table (Watt et al ., ; Doherty & Watt, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, no conclusive argument could be made regarding a measurable and crystal quality related property, and the shock sensitivity of a cast PBX. Additional research was carried out at the crystal level using line broadening in nuclear quadrupole resonance (Doherty et al ., ) and in X‐ray diffraction (Förter‐Barth et al ., ), a modified differential scanning calorimetric method (Spyckerelle, ; Spyckerelle et al ., ), SEM applied to cleaved crystal surfaces (Van der Heijden et al ., ; Van der Heijden & Bouma, ), impact testing with a ballistic impact chamber (Bouma et al ., ) and nanoindentation (Hudson et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Their results showed that reducing the particle size of explosive crystals in plastic bonded explosives decreased sensitivity to impact initiation. Another important finding indicated that the influence of particle size on the impact initiation can only be observed when particle size is sufficiently small, even less than 50 nm [15].…”
Section: Comparing Laser and Impact Ignition Energiesmentioning
confidence: 98%
“…For energetic materials it is thought that the initiation of an explosion can be caused by an unintentional shock wave hitting a defect upon its propagation through a crystal. It has been demonstrated that the higher the product quality of a solid energetic material, the less sensitive a plastic-bonded explosive containing this energetic material becomes [2]. A reduced sensitivity means that the detonation threshold is higher which would prevent unintentional detonations, therefore, these explosives are safer to handle.…”
Section: Introductionmentioning
confidence: 97%